Efficient Cas9‐based Genome Editing Using CRISPR Analysis Webtools in Severe Early‐onset‐obesity Patient‐derived iPSCs. Issue 8 (11th August 2022) - Patel, Achchhe; Iannello, Grazia; Diaz, Alejandro Garcia; Sirabella, Dario; Thaker, Vidhu; Corneo, Barbara
Abstract: The CRISPR system is an adaptive defense mechanism used by bacteria and archaea against viruses and plasmids. The discovery of the CRISPR‐associated protein Cas9 and its RNA‐guided cleavage mechanism marked the beginning of a new era in genomic engineering by enabling the editing of a target region in the genome. Gene‐edited cells or mice can be used as models for understanding human diseases. Given its high impact in functional genomic experiments on different model systems, several CRISPR/Cas9 protocols have been generated in the past years. The technique uses a straightforward "cut and stitch" mechanism, but requires an accurate step‐by‐step design. One of the key points is the use of an efficient programmable guide RNA to increase the rate of success in obtaining gene‐specific edited clones. Here, we describe an efficient editing protocol using a ribonucleotide protein (RNP) complex for homology‐directed repair (HDR)–based correction of a point mutation in an induced pluripotent stem cell (iPSC) line generated from a 14‐year‐old patient with severe early‐onset obesity carrying a de novo variant of ARNT2 . The resulting isogenic iPSC line, named CUIMCi003‐A‐1, has a normal karyotype, expresses stemness markers, and can be differentiated into progenies from all three germ layers. We provide a detailed workflow for designing a single guide RNA and donor DNA, and for isolating clonal human iPSCs edited with the desired modification. This article also focuses on parameters to consider when selecting reagents for CRISPR/Cas9 gene editing after testing their efficiency with in silico tools. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Design of sgRNAs and PCR primers Basic Protocol 2 : Testing the efficiency of sgRNAs Basic Protocol 3 : Design of template or donor DNA Basic Protocol 4 : Targeted gene editing Basic Protocol 5 : Selection of positive clones Basic Protocol 6 : Freezing, thawing, and expansion of cells Basic Protocol 7 : Characterization of edited cell lines